Computer Aided Reverse Engineering with Renishaw Digitizer for Digitization and Mazak for Model Fabrication - Azlan Bin Mohamed Adnan, Azlan (Universiti Teknologi Petronas, 2008)
Application of reverse engineering (RE) is gaining its popularity in product design and manufacturing in recent years. It takes whatever methods, manual or computer-aided methods, to duplicate an existing object or system, either hardware or software. This report discovers about the process of exploring technical challenges to automatically generate computer-aided design (CAD) of an existing part using touch probe imaging techniques. This concept, computer-aided reverse engineering system has a potential for faster model duplication over traditional reverse engineering technologies. RENISHAW 3D Laser Digitizer was used to digitize the object and then the models were saved in IGES file format. CATIA CAD then has been used to create the solid model of the object, and finally the laminated object will be manufactured using MAZAK machine. In this project, a soccer boot has been reverse engineered. A prototype of the shoe was fabricated using the CNC codes that were obtained from UG NX3. The methodology of this process was presented, and this case study illustrated the RE approach. Technical challenges and future research directions in computer aided reverse engineering were identified. This approach has proved that, CAD Reverse Engineering increased the effectiveness in remodeling a product. These benefits include to reduce the time consume when generating the coordinates and also to get an accurate dimension of the object. It means that, complex contours of the shoe can be machined accurately by using this approach.